FRI0026 Identification of micrornas candidates specifically expressed in monocytes of undifferentiated arthritis patients who progressed to rheumatoid arthritis. (15th June 2017) - Kurowska, W; Kuca-Warnawin, E; Radzikowska, A; Ciechomska, M; Skalska, U; Jakubaszek, M; Kwiatkowska, B; Maslinski, W
Abstract : Background: Monocytes are central to the initiation of inflammation and bone erosion in rheumatoid arthritis (RA). Therefore, understanding of molecular pathways regulation in monocytes, especially at the early stages of RA development, is of crucial importance as it may help to predict the progression to the full-blown disease. However, mechanisms of gene regulation in monocytes, particularly the pattern of microRNA molecules (miRNAs) expression which can be involved in regulation of several cellular inflammatory pathways, in early phases of RA (i.e. at undifferentiated arthritis-UA stage) are not fully characterized. Objectives: To investigate the pattern of miRNAs expression in monocytes that could serve as new biomarkers for RA development. Methods: Magnetically sorted monocytes from peripheral blood of 19 patients with UA served for total RNA isolation. Total RNA from both sample and reference was labelled with Hy3 and Hy5 fluorescent label, respectively, using the miRCURY LNA microRNA Hi-Power Labeling Kit (Exiqon, Denmark). Fluorescent labelled samples and a reference RNA sample were hybridized to the miRCURY LNA microRNA Array 7th Gen (Exiqon), followed by scanning by Microarray Scanner System (Agilent Technologies, USA). The image analysis was carried out using ImaGene 9 Software (Exiqon). Results: Out of 19 patients with UA enrolled in the study, 12 were verified for diagnosis after 4 years of follow-up (7 patients did not respond to the call for re-evaluation). Four patients developed full-blown RA (UA→RA patients), 6 patients remained still in UA phase (UA→UA patients), 1 patient was diagnosed as having Sjögren's Syndrome, and 1 undifferentiated connective tissue disease. Baseline characteristics of UA→RA vs UA→UA patients were as follows: age (median: 50.5, range 37–59 years vs 52.5, range 32–63 years), CRP (median: 9.0, range 1–22 mg/l vs 8.0, range 1–21 mg/l), ESR (median: 37.0, range 4–47 mm/h vs 34.0, range 15–44 mm/h) and swollen joins count (median: 3.0, range 1–9 vs 2.5, range 1–4). Following computational unsupervised analysis we identified 50 miRNAs in monocytes that have the largest variation across all patients samples. From these 50 miRNAs we selected several specific miRNA candidates on the basis of significantly changed expression in monocytes of UA→RA vs UA→UA patients. Predicted specific miRNAs targeting inflammatory genes in monocytes of UA→RA patients are: miR-483–3p (2.7-fold increased, p=0.009), miR-378d (4.1-fold decreased, p=0.0059), miR-371b-5p (52.8-fold increased, p=0.0381) miR-642b-5p (13.7-fold increased, p=0.0380), and miR-25–3p (1.8-fold decreased, p=0.0317). Additional validation of selected miRNAs candidates will be further performed using qPCR analysis. Conclusions: Our results indicate new miRNA candidates differentially expressed in peripheral blood monocytes from patients with UA who subsequently developed RA, in comparison to patients with UA who did not progress to RA after 4 years follow-up. Acknowledgements: Supported by NCN Poland (grant 2012/06/A/NZ5/00059). Disclosure of Interest: None declared